2018
DOI: 10.22454/fammed.2018.631070
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Incoming Medical Students’ Attitudes

Abstract: Background and Objectives: The Warren Alpert Medical School of Brown University (AMS) recently implemented a novel dual degree MD-ScM program in primary care and population medicine (PC-PM) that enrolls up to 24 of its nearly 144 yearly matriculants. The overarching goal of this track is to train medical students to become physician leaders who focus on issues in population medicine within primary care. Methods: We conducted a baseline assessment of the students enrolled in this parallel track in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Similarly, Gutiérrez et al (2020) studied various active methodologies, including transmedia narrative supported by ICTs, resulting in improved learning strategies, a deeper understanding of the topics, enhanced problem-solving, and increased classroom satisfaction, without distinguishing between SDs and DDs. Monteiro et al (2018) found that students demonstrated slightly more significant differences in their attitudes towards culture, professionalism, and serving underserved populations when engaged in collaborative work, as compared to SD students. Calvert (2022) using traditional methodology, compared the performance (grades) of DD students in management and engineering with two SDs programs, concluding that DD students achieved the same level of specialization engineering and business administration.…”
Section: Single-and Double-degrees In Social Sciencesmentioning
confidence: 82%
“…Similarly, Gutiérrez et al (2020) studied various active methodologies, including transmedia narrative supported by ICTs, resulting in improved learning strategies, a deeper understanding of the topics, enhanced problem-solving, and increased classroom satisfaction, without distinguishing between SDs and DDs. Monteiro et al (2018) found that students demonstrated slightly more significant differences in their attitudes towards culture, professionalism, and serving underserved populations when engaged in collaborative work, as compared to SD students. Calvert (2022) using traditional methodology, compared the performance (grades) of DD students in management and engineering with two SDs programs, concluding that DD students achieved the same level of specialization engineering and business administration.…”
Section: Single-and Double-degrees In Social Sciencesmentioning
confidence: 82%